Autosomal control of the Y-chromosome kl-3 loop of Drosophila melanogaster. - Piergentili, R.; Bonaccorsi, S.; Raffa, G.D.; Pisano, C.; Hackstein, J.H.; Mencarelli, C. (Chromosoma, 2004)
The Y chromosome of Drosophila melanogaster carries a limited number of loci necessary for male fertility that possess a series of unconventional features that still hinder a definition of their biological role: they have extremely large sizes; accommodate huge amounts of repetitive DNA; and develop prominent, lampbrush-like loops that bind a number of non-Y-encoded proteins. To obtain insight into the functional role of the loop-forming fertility factors, we characterized four autosomal male-sterile mutations that identify two loci we named loop unfolding protein-1 (lup-1) and loop unfolding protein-2 (lup-2). Biochemical and ultrastructural analysis revealed that neither of them impairs the synthesis of the putative dynein subunit encoded by the ORF localized within the kl-3 fertility factor. However, the stability of four dynein heavy chains is simultaneously affected in each mutant, together with the regular assembly of the axonemal dynein arms that are either absent or strongly reduced. These results indicate that the synthesis of the kl-3-encoded dynein can be uncoupled from the formation of the corresponding loop and suggest that this structure does not simply represent the cytological counterpart of a huge transcription unit, but must be regarded as a complex organelle serving some additional function necessary for male fertility.